Tabularność wiersza wolnego i jej konsekwencje lekturowe - Skibski, Krzysztof (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2013)
This article touches upon the tabular nature of free verse; here it indicates the individuality of verses in the text structure resulting from its non-linear character (spatiality) as a result of free verse. In other words, any text written in free verse is potentially a structure of coincidental syntax e.g. as a result of maximised equivalence each single verse is semantically independent and primarily independent with respect to syntax from the other verses. This article relies on the assumption that reception of a text written in free verse is non-linear and therefore tabular. This assumption is based on a conviction that the tabular nature is not a revelation of the new media or the change in perceiving texts propagated in the new media. Rather, it is a phenomenon typical of poetry; it started to accompany poetry when the notion of free verse was introduced. The text is illustrated with examples of poems by contemporary Polish authors.